Unidentified Remains: The Impolitics of Non-Identity - Latchford, Frances J. (Atlantis, 2014)
For some time now, queer theory has uncritically assumed that identity politics should be rejected outright. Through a theoretical and biographical discussion of Michel Foucault’s resistance against the subject—his attempts at subject effacement—this paper argues that resistance is not realized through non-identity politics alone. It addresses two main questions: does the practice of non-identity sufficiently resist knowledge that (re)presents subjects and what are the social and political possibilities or risks of subject effacement? In response to these questions, it argues that, although the queer politics of non-identity is a mode of resistance, it is not sufficient as resistance in all contexts or fields of knowledge. It suggests that in many contexts, what Foucault refers to as the “infinite possibility of self” or the interruption of the subject cannot be realized through invisibility politics: in many contexts this possibility can only be experienced if and when the subject comes face to face with the presence of an other-subject.